The role of human resource management on employee performance in the management of Pekalen rafting tourism in Probolinggo - Khotijah Maimunah; Amelia Citra Dewi; M Ariel Ikhsan; M Feri Hardiyanto; Ahmad Riadus Solihin; Yeni Kartikawati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the role of human resources on employee performance in managing rafting tourism in Probolinggo. The adventure tourism industry, especially rafting tourism, requires optimal human resource management to ensure tourist satisfaction, safety, and business sustainability. This study uses a descriptive qualitative approach with a case study method on Pekalen Rafting tourism in Probolinggo. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation studies with informants consisting of managers, rafting guides, operational staff, and support employees. The results of the study indicate that the role of human resources, including the recruitment process, training and development, and a fair compensation system, has a positive effect on employee performance in managing Pekalen Rafting tourism in Probolinggo. Good employee performance is reflected in the level of operational safety, customer satisfaction, and service efficiency. The conclusion of this study confirms that the role of human resources on employee performance is a key factor in increasing the competitiveness and sustainability of rafting tourism businesses.